Feminization of teaching: gender and motivational factors of choosing teaching as a career - Kammermeier, Marina; Muckenthaler, Magdalena; Weiß, Sabine; Kiel, Ewald (Frontiers in Education, 2025)
IntroductionThe feminization of the teaching profession is widely discussed internationally. In light of current debates on changes in the perception of gender roles and gender diversity, it is important to examine whether students’ motives for choosing the teaching profession vary by gender.MethodsTo explore this question, we assessed student teachers’ motives for choosing teaching as a career as well as their perception of future demands and abilities to cope with stress using an online tool.ResultsFemale students showed higher pedagogical, altruistic, and idealistic motivations, while male students had higher subject-related motivation and more often chose teaching as a fallback career. In addition, female students displayed greater openness to professional cooperation, interest in students’ social and cultural diversity, and less avoidance of social support under stress.DiscussionThese results support theories that gender role expectations influence perceptions of occupational gender fit.